Curriculum review: from theory to practice / Saidatul Akmar Zainal Abidin ...[et al.] - Zainal Abidin, Saidatul Akmar; Abdullah, Normah; Jamil, Asiah; Ramlan, Zarina Suriya (Universiti Teknologi MARA Shah Alam, 2017)
Currently, education is facing overwhelming challenges in terms of the generation of students that the universities are taking in and the demands of the industry. This is propagated further by the enhancement of modern technology. Therefore, the courses offered in universities must ensure that graduates are ready for the working world and a good well rounded curriculum is needed to achieve this. In Malaysia, the body governing academic quality is the Malaysian Qualifications Agency (MQA) and they require curriculums to be reviewed every 3 - 5 years to ensure their relevance to industry requirements. A curriculum usually undergoes years of 'trials' and changes before a sound one can be produced. In essence, a curriculum needs to be reviewed for the following reasons; the dynamic nature of a curriculum, to keep abreast with new approaches in learning and teaching and best practices in teaching strategies. Students need to be trained and well-exposed to meet the challenges of the globalised world and function well at the workplace. Due to these reasons, the paper discusses the processes involved in reviewing a curriculum. A program from the Academy of Language Studies in UiTM Malaysia was selected as a case to highlight the stages, challenges and outcomes of the review.